Pengaruh Aspek Perilaku dalam Meningkatkan Pendapatan Nelayan di Wilayah Pesisir Kabupaten Aceh Timur - Rozalina, Rozalina; Indra, Siti Balqies; Sari, Riezky Purnama (Universitas Medan Area, 2024)
This research was conducted in East Aceh Regency, determining the research location using purposive sampling (intentional). The object of this research is fishermen in East Aceh Regency in 2022. Sampling was carried out using a disproportionate stratified random sampling technique, namely by selecting 5 sub-districts (Birem Bayeun, Ranto Selamat, Sungai Raya, Idi Rayeuk and Nurussalam) in the coastal area with the largest number of fishermen, Then from the 5 (five) sub-districts, 20 fishermen each were taken using the incidental method as samples, the number of selected samples was 100 people. The scope of this research is the knowledge, attitudes and skills of fishermen, as well as fishermen's income, carried out in July-August. The results of research to see reliability with Cronbach's alpha obtained α = 0.613 0.6, meaning that all items from the statement can be trusted to be studied. From the results of the analysis, behavioral aspects influence the increase in fishermen's income. Partial testing (t test) showed that knowledge and attitudes had an effect on income, while the skills variable had no effect. The simultaneous test (F test) of the influence of behavioral aspects on income shows influential results.